Pandemic Media : Preliminary Notes toward an Inventory - Keidl, Philipp Dominik; Melamed, Laliv; Hediger, Vinzenz; Somaini, Antonio; Keidl, Philipp Dominik; Melamed, Laliv; Hediger, Vinzenz; Somaini, Antonio (meson press, 2020)
With its unprecedented scale and consequences the COVID-19 pandemic has generated a variety of new configurations of media. Responding to demands for information, synchronization, regulation, and containment, these (3z(Bpandemic media(3y (Breorder social interactions, spaces, and temporalities, thus contributing to a reconfiguration of media technologies and the cultures and polities with which they are entangled. Highlighting media$1 (Bs adaptability, malleability, and scalability under the conditions of a pandemic, the contributions to this volume track and analyze how media emerge, operate, and change in response to the global crisis and provide elements towards an understanding of the post-pandemic world to come.s
English
Keywords: Media studies; Nonbooks, PBS / Medien, Kommunikation/Medienwissenschaft; Medienwissenschaften: Internet, digitale Medien und Gesellschaft; Coronavirus; Media; Scale; Technologies; Time; Materialities; Digitalization; Activism; Space; Sociability; Instruction; COVID-19; Pandemic; Education; Temporality; Film, Kino; Internet und digitale Medien: Kunst und Performance; Film-, Fernseh-, Radio-Genres: Science-Fiction, Fantasy und Horror